Estudio de factibilidad para la implantación de una empresa de servicios de mantenimiento actualización y reparación de equipos de computación con servicio a domicilio en la ciudad de Loja. - Gutiérrez Sánchez, Glendy Narcisa (2012)
The administration in our city, is guided however toward the satisfaction of the plaintiffs' necessities in what has to see to maintenance and repair of computers in the homes, when carrying out the comparisons with the necessary investment utility it is obtained, but it would be very beneficial to carry out bigger investments to future in space, personal and mobile team, to satisfy to the market that one cannot assist, the utilities are also acceptable although credits that it is necessary to cancel monthly for the purchase of active exist as, vehicles and team that it is needed when beginning activities. The present thesis will have a 5 year-old useful life and its installation will be in the city of Loja in the Neighborhood Tall Flores he/she Looks (Via old to Catamayo), for the easiness of mobility toward different points of the city, also to have easiness for the placement of a ship of attention. In the market study that the city of Loja is constituted, as for repair services and maintenance of computers has been obtained an unsatisfied demand of 336.649 times to the first year, that which represents a significant available market, even taking in consideration that the service is very comfortable, but not all the proprietors manifested having problems for this type of service, however the unsatisfied demand is wide, and the company has taken an installed capacity of attention of 4160 annual services, but for beginning of activities he/she has settled down to participate in the market with 3744 annual services, to assure a suitable managerial administration in our city, the final price that you will get paid is also of $19,54 for the first year. In the technical study you could determine that the vehicles and team to use are of easy acquisition in our half one and they are not rather of high technology of frequent use in light transport and communications, in a same way the materials for the application of the service and more necessary inputs, as the radii the antennas etc., are them in our half one and one would not have problems in the event of maintenance or repair. On the other hand, the process of attention will be directed and controlled by people with experience, In what refers to the investments that are of 32.278,41 dollars and the financing with the Bank of Loja that is of 13.000,00 dollars, he/she settles down that they are not exaggerated the machinery and team since they are the basic ones, the legal structuring is also carried out it for an only time, and in what has to see to active circulating or work capital, this he/she will have a monthly rotation since the services they will be canceled in an immediate way, reason why he/she is formed a work capital with a permanent monthly recovery. Likewise, the financial indicators as the VAN of the present project give us a positive value 38.054.91 that which assures that the investment has a significant value after the 5 years of useful life of the project. Also for the present project the TIR is 50.33% being this bigger value to the rates to fixed term of the bank, and even very superior to that of other projects and it is not extreme, reason why the project is acceptable and executable. It has been obtained the relationship I also benefit cost, same that it assures that for each dollar that owes the company one has 1.30 cents to pay, that which reflective great liquidity, and profitability of 30% for each invested dollar; the values of sensibility, reflect that the company supports 5.85 increment% in the costs and 4,49 decrease% in revenues, reason why the project is acceptable when granting an error margin in market calculations, technicians and financial. Regarding the organization of the company, this it is of Limited Responsibility and it will be conformed by the General Meeting of partners, Manager, Advisory Juridical, Secretary, Accountant and the necessary personnel for the process of the service.